Catecholamines: Knowledge and understanding in the 1960s, now, and in the future. (January 2019) - Stanford, S. Clare; Heal, David J.
The late 1960s was a heyday for catecholamine research. Technological developments made it feasible to study the regulation of sympathetic neuronal transmission and to map the distribution of noradrenaline and dopamine in the brain. At last, it was possible to explain the mechanism of action of some important drugs that had been used in the clinic for more than a decade (e.g. the first generation of antidepressants) and to contemplate the rational development of new treatments (e.g. l -dihydroxyphenylalanine therapy, to compensate for the dopaminergic neuropathy in Parkinson's disease, and β1 -adrenoceptor antagonists as antihypertensives). The fact that drug targeting noradrenergic and/or dopaminergic transmission are still the first-line treatments for many psychiatric disorders (e.g. depression, schizophrenia, and attention deficit hyperactivity disorder) is a testament to the importance of these neurotransmitters and the research that has helped us to understand the regulation of their function. This article celebrates some of the highlights of research at that time, pays tribute to some of the subsequent landmark studies, and appraises the options for where it could go next.